FAME production from residual materials: Optimization of the process by Box-Behnken model - E. M. Vargas; J. L. Ospina; L. A. C. Tarelho; M. I. Nunes (Energy Reports, 2020)
In the worldwide more than 95% of biodiesel production feedstocks come from edible oils. The waste cooking oils (WCO) are an alternative feedstock for biodiesel production; its usage reduces significantly the cost of biodiesel production and has environmental benefits, e.g., a waste recovery instead of its elimination. This work aimed to optimize the process to produce fatty acid methyl esters (FAME) using the response surface methodology and a Box-Behnken experimental design from mixtures of refined palm oil (RPO) with WCO using a residual solid material as catalyst (biomass fly ashes). The influence on FAME yield of four operational variables (catalyst loading, methanol/oil molar ratio, RPO/WCO ratio and reaction temperature) was studied. The higher FAME yield achieved using the RMS method was 77.06% for: 14.63 wt% of catalyst loading, 5.42/1of methanol/oil molar ratio, 14.81 wt% of RPO in the oil mixture and 55~°C for the reaction temperature.
Keywords: 330; Optimization; Biomass fly ash; FAME; Refined palm oil; Response surface methodology; Solid catalyst; Waste cooking oil